Side elevation of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
North-facing elevation of the Mandaleshwar Mahadev temple which has the main temple body built in stone and the shikhara in brick. Kutastambhas (miniature shikhara models atop pillar motifs) in the recesses of the temple wall.